2021
DOI: 10.1021/acs.jmedchem.1c00327
|View full text |Cite
|
Sign up to set email alerts
|

Macrolide Inspired Macrocycles as Modulators of the IL-17A/IL-17RA Interaction

Abstract: Interleukin 17 (IL-17) cytokines promote inflammatory pathophysiology in many autoimmune diseases, including psoriasis, multiple sclerosis, rheumatoid arthritis, and inflammatory bowel disease. Such broad involvement of IL-17 in various autoimmune diseases makes it an ideal target for drug discovery. Psoriasis is a chronic inflammatory disease characterized by numerous defective components of the immune system. Significantly higher levels of IL-17A have been noticed in lesions of psoriatic patients, if compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…When Ensemble 159 was profiled in a human epidermal keratinocyte (HEKa) assay, stimulated by IL-17A and TNFα to release the pro-inflammatory cytokine IL-8, a functional EC 50 of 151 nM at inhibiting IL-8 secretion was observed. To examine this finding further, LEO Pharma A/S entered into a partnership with Fidelta to explore alternative macrocyclic templates, including those based on azithromycin, and some of that work has been published …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When Ensemble 159 was profiled in a human epidermal keratinocyte (HEKa) assay, stimulated by IL-17A and TNFα to release the pro-inflammatory cytokine IL-8, a functional EC 50 of 151 nM at inhibiting IL-8 secretion was observed. To examine this finding further, LEO Pharma A/S entered into a partnership with Fidelta to explore alternative macrocyclic templates, including those based on azithromycin, and some of that work has been published …”
Section: Introductionmentioning
confidence: 99%
“…To examine this finding further, LEO Pharma A/S entered into a partnership with Fidelta to explore alternative macrocyclic templates, including those based on azithromycin, and some of that work has been published. 43 The joint research team tested intermediates to explore the SAR and the role of the macrocycle and, in doing so, identified nonmacrocycles, such as compound 1 (EC 50 = 575 nM), that showed the macrocycle was not required for activity. Structural information is particularly important when targeting PPIs, as without it, it can be difficult to tell where the ligand is binding to the protein and, therefore, to rationally make changes to improve the potency.…”
Section: ■ Introductionmentioning
confidence: 99%
“…56 However, a number of small molecule inhibitors that target IL-17A have been reported. [16][17][18][19] Of these, perhaps the best studied have been based on the series of macrocycles patented by Ensemble, 23 which have been shown to bind in the central binding pocket. Previous crystallographic studies of IL-17:peptide:ligand complexes have suggested that these inhibitors of IL-17 function either by sterically blocking and/or inducing structural changes that preclude receptor binding.…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative assessment of the binding isotherms of the IL-17AA and IL-17AF isoforms to IL-17RA suggest similar k on values, however notably the IL-17AA isoform shows no dissociation during the course of the experiment, whereas IL-17AF has a measurable k off . Previous studies 16,17,19 have suggested that small molecule inhibitors function by either causing structural changes that prevent receptor binding or by causing steric clashes. Our experiments, run in the presence of MC, suggests that IL-17AA binds both MC and IL-17RA simultaneously as only signicant effects on k off are observed resulting in approximately a 3-4-fold weaker K D .…”
Section: Impact Of Ligand Binding On Il-17 Structure and Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation